The Role of Social Media in Enhancing Communication and Collaboration in Business - Okonkwo, Ifeanyi; Awad, Hisham Abubaker (Tecno Scientifica Publishing, 2023)
The study aimed to highlight the importance of effective communication and collaboration in modern business, and how social media can be used as a vital tool to connect with customers, employees, and other stakeholders in new and innovative ways. Effective communication and collaboration are essential to the success of any business, particularly in the modern era, where competition is intense and innovation is required to stay competitive. To accomplish their goals, businesses must be able to communicate ideas, feedback, and information efficiently and effectively. Social media has become an indispensable instrument for connecting with customers, employees, and other stakeholders in novel and creative ways, resulting in increased innovation, enhanced productivity, and a more engaged and motivated workforce. Businesses can improve their knowledge transfer processes and foster a culture of continuous learning and innovation by leveraging social media platforms. Favourable network externalities in social media refer to the favourable effects that result from an increase in social media platform usage. This allows businesses to reach a larger audience and increase brand recognition. Social media can also provide valuable insights into customer behaviour and preferences, allowing businesses to tailor their marketing strategies and products to suit their customers' needs. Social media monitoring is essential for the growth of business capital because it enables businesses to measure their online reputation and respond promptly to any negative comments or feedback. However, social media has been linked to melancholy, anxiety, and addiction. Therefore, businesses must take steps to mitigate the negative effects of social media on the mental health of their employees, such as providing mental health support services and promoting healthy social media usage.